Kebolehgunaan (Usability) Modul Ajar Discovery Learning Materi Bangun Datar Matematika Kelas IV - Nuni Sri Wahyuni; Dede Tri Kurniawan; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Teaching modules have an important role as a support for teachers in designing the learning process. In preparing learning tools, the teacher plays a major role. This trains teachers' thinking abilities to innovate and develop effective teaching modules. The ability to think creatively in mathematics is an ability that every student needs to have to analyze mathematical problems from different points of view, then solve them in various ways and produce varied creative ideas. One learning approach that is currently widely applied is Discovery Learning. This research aims to test the feasibility or usability of open modules using the Discovery Learning approach on plane material for class IV students. This research uses quantitative research, namely a survey method in the form of a questionnaire using SmartPLS software to manage the data. The research results show that the measurement analysis model of the variables tested shows that the Cooperative/Collaborative Learning variable shows a higher value than several other variables and explains more variance than other indicators. In this diagram, we can see that the AP value is the highest, with a value of around 0.756. Meanwhile, the lowest value is the variable 0.4 from the other variables.